A COMPARATIVE STUDY ON THE EFFECT OF HIGH HYDROSTATIC PRESSURE ON RIPENING OF TURKISH WHITE CHEESE FROM DIFFERENT MILK SPECIES - YAMAN, H.; SARICA, E.; COŞKUN, H. (Italian Journal of Food Science, 2020)
High pressure treatment has diverse effect on cheeses depending on their characteristics. In this study, pressure application on Turkish White cheese (300 and 450 MPa/5 min) and the changes during ripening were investigated. The 450 MPa pressure process showed an enhanced effect on proteolytic and lipolytic activity of cheeses. Besides, 450 MPa pressure treatment was very effective on the microbiological profile, but the other treatment condition exhibited a more moderate antimicrobial effect. Although, the total mold-yeast were detected after high-pressure treatment, their existence to a considerable degree was seen at the end of storage.